2015
DOI: 10.1111/jjns.12099
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depressive symptoms in older Japanese primiparas at 1 month post‐partum: A risk‐stratified analysis

Abstract: These results highlight the importance of early assessment of depressive symptoms and the provision of continuous care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Out of these, text screening yielded 20 (17%) papers on India and 67 papers (8%) on Japan. Finally, 15 papers (13%) on India [ 10 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 35 papers (4%) on Japan [ 7 , 8 , 9 , 14 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were included in the review. Thirty-seven papers (India, n = 5; Japan, n = 32) were excluded because they did not...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these, text screening yielded 20 (17%) papers on India and 67 papers (8%) on Japan. Finally, 15 papers (13%) on India [ 10 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 35 papers (4%) on Japan [ 7 , 8 , 9 , 14 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were included in the review. Thirty-seven papers (India, n = 5; Japan, n = 32) were excluded because they did not...…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we selected two countries: India and Japan. These countries were selected because their social and cultural aspects (such as family structures, fertility rate, and childrearing cultures) clearly differ from each other, although perinatal depression is prevalent in both India and Japan (India: antenatal depression, 6–26.3%; postnatal depression, 7.5–45.5%; Japan: antenatal depression, 5.6–5.8%; postnatal depression, 5.0–21.5%) [ 7 , 8 , 9 , 10 ]. India, located in South Asia, is the second most populous country in the world (over 1.2 billion people) with a total fertility rate of 2.4 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mental status of mothers considered to have low levels of oxytocin associate with incomplete breastfeeding seemed to be stable. Therefore, in social environments and/or clinical characteristics of pregnant Japanese women, there may be some serious risk factors for postpartum depression other than the status of breastfeeding, such as personal and family factors, socioeconomic status, support from other family members and personal plans for furthering careers [4][5][6][7][8] . For example, in our recent Japanese study that asked mothers' biggest worry at two weeks after delivery, only 10% reported anxiety about breastfeeding 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum depression has been recognized as the leading medical complication among new mothers 2,3 . To date, some risk factors for postpartum depression, such as personal and family factors, socioeconomic status, support from other family members and personal plans for furthering careers, have been examined [4][5][6][7][8] . Some studies have demonstrated that breastfeeding can protect mothers from postpartum depression and are starting to clarify which biological and psychological processes may explain this protection [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Iwata et al [21] reported that factors such as concerns about infant caretaking and financial burden as well as physical burden in daily life were predictive factors for depression at 1 month postpartum. Thus, factors other than LBPP at 3 months postpartum might be associated with EPDS score.…”
Section: Discussionmentioning
confidence: 99%